2014
DOI: 10.1063/1.4866101
|View full text |Cite
|
Sign up to set email alerts
|

New approach for calibration the efficiency of HpGe detectors

Abstract: Abstract. This work evaluates the efficiency calibrating of HpGe detector coupled with Canberra GC3018 with Genie 2000 software and Ortec GEM25-76-XLB-C with Gamma Vision software; available at Neutron activation analysis laboratory in Malaysian Nuclear Agency (NM). The efficiency calibration curve was constructed from measurement of an IAEA, standard gamma-point sources set composed by 214 Am, 57 Co, 133 Ba, 152 Eu, 137 Cs and 60 Co. The efficiency calibrations were performed for three different geometries:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…5 shows that the flux reduces in a linear fashion for the 0.05 cm cladding thickness resulting in a neutron flux reduction by 14.5 %. The result is consistent with the observation that has been made according to the behaviors of the thermal neutron flux, which is the dominant neutron flux in the reactor (neutrons are well thermalized with about 95 % of thermal over epithermal neutrons) [9]. The axial thermal neutron flux at full core power of 750 kW is presented in Fig.…”
Section: Resultssupporting
confidence: 91%
“…5 shows that the flux reduces in a linear fashion for the 0.05 cm cladding thickness resulting in a neutron flux reduction by 14.5 %. The result is consistent with the observation that has been made according to the behaviors of the thermal neutron flux, which is the dominant neutron flux in the reactor (neutrons are well thermalized with about 95 % of thermal over epithermal neutrons) [9]. The axial thermal neutron flux at full core power of 750 kW is presented in Fig.…”
Section: Resultssupporting
confidence: 91%
“…Granite is widely distributed throughout the continental crust and presents the most abundant plutonic rock present in mountain belts. Because of the large quantities of granite that occur in nature, geologists believe that most granites had been formed either by melting, partial melting or metamorphosis of deeply buried shale and sandstone (Alnour 2012). Some granite has been reported to have higher radioactivity, thereby raising some concerns about their safety.…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of 40 K, all gamma lines have a high branching ratio [11]. The efficiency curve (Fig 3) covers the photon energy range 121.78-1528 keV with a fitting polynomial of order 4, as given by Alnour et al PLOS ONE [12] and Gouda et al [13], shown in (1) below:…”
Section: Competing Interestsmentioning
confidence: 93%